Crime, fear and continuous traumatic stress in South Africa: What place social cohesion? - Eagle, Gillian (PINS-Psychology in Society, 2024)
International literature on crime and violence suggests that social cohesion may play a key role in facilitating prevention at community level. It is argued that in South Africa high levels of crime entailing interpersonal violation not only reflect ruptures in the social fabric but also contribute to social disorganization. In exploring the traumatic impact of exposure to fairly pervasive criminality via the constructs of Fear of Crime (FoC) and Continuous Traumatic Stress the article explores some of the linkages between responses to crime and the facilitation or erosion of potentialities for social cohesion. It is argued that the common responses of fearfulness, suspicion and social withdrawal (as well as defensive aggression in some instances) are counter-productive to attempts to build pro-social organization. Consequently a rather intractable circular relationship may ensue in which the conditions that enable criminality are not challenged because indirect and direct exposure to violation, alongside perceived and actual deficits in formal state interventions, have eroded the motivation and capacity of citizens to tackle such conditions, leaving spaces open for violation to continue unchecked, Some of the complexities of thinking about forms of social cohesion as a route to challenge crime and its impact in South Africa are elaborated. It is emphasized that collective efficacy appears to be the aspect of social cohesion that is most pivotal in addressing this feature of society.